Semiotic Analysis Of Exemplary Messages In The Buya Hamka Movie Vol I 2023 - jazir jazir; Rosyidi Rosyidi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2025)
Seeing the development of the times, increasingly sophisticated information and communication technology has given rise to various bad behaviors that make the Indonesian people, especially young people, lose their spirit of jihad and nationalism, become mentally weak, often toxic, and lazy, one form of preventing this decline is to utilize mass media in the form of movies, because movies are one of the most popular at the moment, so by utilizing movies as a medium of invitation or da'wah, by using example as a method, stubborn young people can be melted, therefore, the problem raised in this research is how to analyze the exemplary message in the Buya Hamka Movie Vol I 2023. To be able to analyze the exemplary message in the movie, the researcher used a qualitative descriptive approach with Roland Barthes' type of research in the form of three meanings in the analysis, namely denotation, connotation and myth. Meanwhile, data collection techniques use observation and documentation techniques. Checking the validity of the research uses in-depth observation and triangulation so that researchers can analyze speech, behavior, signs and movie soundtracks. As for the results of this research, there were seventeen scans containing exemplary messages in the Buya Hamka Movie Vol I. From the results of this research, it was found that messages of faith, sharia and morals were more dominant in the moral messages which recommended increasing the number of good and non-toxic words.